Age, growth and demographic characteristics of Sillago flindersi exploited in a multi-species trawl fishery - Gray, C.; Barnes, L.; Ochwada-Doyle, F.; van der Meulen, D.; Kendall, B.; Robbins, William (2014)
© 2014, Japanese Society of Fisheries Science.This study investigated variability in the growth, length, and age compositions and the rates of mortality of Flinders’ sillago Sillago flindersi exploited in a demersal trawl fishery in eastern Australia. Sampling was done over 2 years across three depth strata at two locations approximately 400 km apart. Ageing of sectioned sagittal otoliths indicated that the observed maximum age of females was 6 years and that of males 5 years, that growth was variable and that the von Bertalanffy growth parameters significantly differed according to gender and location. Females attained a greater L8 than males, but males displayed greater k values. The L8 values of both sexes and the mean length-at-age for fish aged 3–5 years were greater at the location of highest latitude. Length and age compositions differed according to depth, with smaller (<15 cm FL) and younger (<2 years) fish generally more predominant in the shallow (<30 m) strata than in the deeper (>31 m) strata. S. flindersi appear to use the shallow strata as a juvenile habitat, moving to deeper waters as they grow. This depth stratification between cohorts may reduce intraspecific competition and could potentially be used as a spatial management tool to reduce any fishing-associated impacts on juveniles. Fish between 1 and 3 years old dominated the age compositions of populations combined across all depths, with estimated total mortality ranging between 2.24 and 2.40. Fishing mortality ranged between 1.54 and 1.70 and was more than twice the derived natural mortality. Exploitation rates were approximately 0.70, indicating that the species was heavily fished.